The significance of time in Augustine's understanding of the authority of scripture - Dingluaia, Lal (2021)
The central thesis of this work is to assert the significance of time to understand the primacy of Scripture, as well as the scope and limitation of scriptural authority, in the mind of Augustine. The first two chapters explore the emergence of the concept of “authority” and “Scripture” that eventually converged into a distinctive theological notion by the time of Augustine. This work asserts that “authority” is the natural outcome of being in a relationship while the need to “commemorate” specific events - most eminently the “Christ-event” - which can subsequently establish cordial relations elevates the status of Scripture as an “authoritative” account. In the next six chapters, this work explores how Augustine’s experience of time as a living, ongoing and creative tension determined his theological stances towards Scripture. It asserts that Augustine, in grappling with the tension of the “now” and “not yet” of the “last days” which the “Christ-event” inaugurated, ultimately interiorized this “temporal” tension, primarily through his reading of Paul, as the “heart” yearning for a “rest”. For Augustine, the authority of Scripture is not propositional but relational, a knowing in fellowship where the eternal Word of God addresses humanity’s deepest need - the “restless heart”. Conversely, negating the veracity of scriptural accounts regarding God’s salvific outworking would amount to shaking the foundation of scriptural authority. The mediating role of Scripture will “cease” beyond the temporal realm when the fulfilment of God’s promises will bring about an unhindered relationship with God. For Augustine, the “restless heart” of vulnerable human beings shall therefore acknowledge the authority of Scripture until the “eternal rest” has been achieved and perfect relationship restored.